Budaya Komunikasi Etnis Minang dalam Film Saiyo Sakato - Winoto, Jessica Vallery; Azeharie, Suzy (Koneksi, 2025)
Film is a communication tool to convey a message to the public regarding certain social phenomena in the form of a story. One social phenomenon that is often highlighted in films is culture. 'Saiyo Sakato' is a film released in 2020. This film has a Minang ethnic background which highlights social phenomena such as the Minang ethnic communication culture. Apart from highlighting the phenomenon of Minang ethnic communication culture, the film 'Saiyo Sakato' conveys the phenomenon of dividing inheritance within the family. This research uses a qualitative approach with descriptive methods and uses Charles Sanders Peirce's semiotic data analysis techniques. The theory used is Charles Sanders Peirce's cultural communication and semiotics. The aim of this research is to find out how the Minang ethnic communication culture is in the film 'Saiyo Sakato'. Data collection methods were carried out by means of observation, interviews, literature study and documentation. The results of research on Minang ethnic communication culture in the film 'Saiyo Sakato' are the culture of maintaining identity, matrilineal culture, Minang boys and the role of mamak in guiding kemenakan. Film merupakan alat komunikasi untuk menyampaikan suatu pesan kepada masyarakat mengenai fenomena sosial tertentu dalam bentuk cerita. Salah satu fenomena sosial yang sering kali diangkat dalam film adalah budaya. ‘Saiyo Sakato’ merupakan film yang dirilis pada tahun 2020. Film ini memiliki latar belakang etnis Minang yang mengangkat fenomena sosial seperti budaya komunikasi etnis Minang. Selain mengangkat fenomena budaya komunikasi etnis Minang, film ‘Saiyo Sakato’ menyampaikan fenomena pembagian harta warisan dalam keluarga. Penelitian ini menggunakan pendekatan kualitatif  dengan metode deskriptif dan menggunakan teknik analisis data semiotika Charles Sanders Peirce. Teori yang digunakan adalah komunikasi budaya dan semiotika Charles Sanders Peirce. Tujuan dari penelitian ini adalah mengetahui bagaimana budaya komunikasi etnis Minang dalam film ‘Saiyo Sakato’. Metode pengumpulan data dilakukan dengan cara observasi, wawancara, studi kepustakaan dan dokumentasi. Hasil dari penelitian budaya komunikasi etnis Minang pada film ‘Saiyo Sakato’ adalah budaya mempertahankan identitas, budaya matrilineal, anak laki-laki Minang dan peran mamak dalam membimbing kemenakan.